The Development of a Learning Package for Caregivers on Developing Emotional Quotient of Preschool Children at Child Development Centers under the Local Government Organizations in Satun Province - Palawan, Kaesorn; Horadal, Arunee; Chatthai, Tassanee (Journal of Information and Learning [JIL], 2022)
The objectives of this research were 1) to develop a learning package for caregivers on developing emotional quotient of Preschool children at child development centers under the Local Government Organizations in Satun Province based on the set efficiency criterion, 2) to compare knowledge and understanding of the caregivers concerning the developing emotional quotient of Preschool children before and after undertaking a learning package, 3) to study the caregivers’ satisfaction toward a learning package on developing emotional quotient of Preschool children. The sample consisted of 34 caregivers at child development centers under the Local Government Organizations in Satun Province, obtained by multistage sampling. The employed research instruments were a learning package on developing emotional quotient of preschool children, a test on knowledge and understanding of caregivers concerning the developing emotional quotient of preschool children, and an evaluation form on caregivers’ satisfaction toward a learning package on developing emotional quotient of preschool children. Statistics employed for data analysis were the E1/E2 efficiency index, mean, standard deviation, and t-test. Research results were as follows: 1) The developed learning package for the caregivers on developing emotional quotient of preschool children at child development centers under the Local Government Organizations in Satun was efficient at 83.17/82.78, thus meeting the set efficiency criterion of 85/85; 2) The post-experiment knowledge and understanding concerning the developing preschool children emotional quotient of caregivers who undertook a learning package was significantly higher than their pre-experiment counterpart at the .01 level of statistical significance; 3) The caregivers were satisfied with the learning package on developing emotional quotient of preschool children at the highest level.